A discovery of witches - Harkness, Deborah E. (New York : Penguin Books, 2011)
Witch and Yale historian Diana Bishop discovers an enchanted manuscript, attracting the attention of 1,500-year-old vampire Matthew Clairmont. The orphaned daughter of two powerful witches, Bishop prefers intellect, but relies on magic when her discovery of a palimpsest documenting the origin of supernatural species releases an assortment of undead who threaten, stalk, and harass her. Deep in the stacks of Oxford's Bodleian Library, young scholar Diana Bishop unwittingly calls up a bewitched alchemical manuscript in the course of her research. Descended from an old and distinguished line of witches, Diana wants nothing to do with sorcery; so after a furtive glance and a few notes, she banishes the book to the stacks. But her discovery sets a fantastical underworld stirring, and a horde of daemons, witches, and vampires soon descends upon the library. Diana has stumbled upon a coveted treasure lost for centuries-and she is the only creature who can break its spell.
Keywords: Vampires -- Fiction; Fantasy fiction